POLITICAL DIALOGUE AS THE BASIS OF FOREIGN POLICY: A CASE STUDY OF MODERN RUSSIAN-GERMAN RELATIONS - N. V. Zaytseva (Vestnik MGIMO-Universiteta)
His article deals with political dialogue as the basis of the progressive development of interstate cooperation and one of the few ways to diminish interstate tensions without use of military force. With the growing list of new threats and challenges it is very important to work out an effective mechanism of interstate cooperation and to use it in foreign policy. Political dialogue helps to form the basis for cooperation between states to ensure the security, political and socio-economic stability of countries. Moreover, the political dialogue in its various forms is no longer a seldom-used private practice. It is the "all-encompassing reality" now the study of which is necessary for understanding of the social, economic, and humanitarian phenomena in the international relations. The author analyzes principles, functions, rules of constructive interstate dialogue, reflects the conditions of the development of a true political dialogue and reveals the situation of its "stylization" The provisions presented in this article are presented from the viewpoint of practical use in the development of a constructive foreign policy. At the same time the author points to their philosophical basis, identifies regularities and characteristics from the standpoint of philosophical knowledge. As a practical demonstration of carrying on the political dialogue the article presents a brief description of Russian-German political relations at the present stage. Bilateral relations between these two countries, based on the rich history, consilience of main positions in resolving of international problems, largely reflect the basic terms and principles of a competent political dialogue.